2021
DOI: 10.3390/jcm10030428
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Recommendation of Motor Imagery Techniques for Rehabilitation after Anterior Cruciate Ligament Reconstruction: A Systematic Review

Abstract: Motor imagery (MI) reported positive effects in some musculoskeletal rehabilitation processes. The main objective of this study was to analyze the effectiveness of MI interventions after anterior cruciate ligament (ACL) reconstruction. A systematic review was conducted from November 2018 to December 2019 in PubMed, Scopus, Web of Science, The Cochrane Library, and Physiotherapy Evidence Database (PEDro). The methodological quality, degree of recommendation, and levels of evidence were analyzed. A total of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…34 This study demonstrates that with simple exercises for AMI, the majority of cases of preoperative extension deficit are easily resolved provided that specific approaches to fatigue the hamstrings and improve quadriceps activation while also influencing neural modulation, providing biofeedback, and facilitating motor excitability are used. 5,7,27,32,44 A further important finding of this study was that the reliability of the Sonnery-Cottet classification of AMI was established with good to excellent interobserver reliabilities.…”
Section: Discussionmentioning
confidence: 60%
“…34 This study demonstrates that with simple exercises for AMI, the majority of cases of preoperative extension deficit are easily resolved provided that specific approaches to fatigue the hamstrings and improve quadriceps activation while also influencing neural modulation, providing biofeedback, and facilitating motor excitability are used. 5,7,27,32,44 A further important finding of this study was that the reliability of the Sonnery-Cottet classification of AMI was established with good to excellent interobserver reliabilities.…”
Section: Discussionmentioning
confidence: 60%
“… 78 However, these trials are limited by inconsistent methodologies, short-term follow-up, and small sample sizes; in a recent systematic review, Pastora-Bernal et al. 81 recommended a need for greater homogeneity between studies to draw evidence-based conclusions regarding the impact of MI in ACLR. Only 2 RCTs included in the review 77 , 80 were adequately powered (N = 101 and N = 58, respectively), with the remaining drawing conclusions from samples of 13, 10, 7, and 5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 RCTs included in the review 77 , 80 were adequately powered (N = 101 and N = 58, respectively), with the remaining drawing conclusions from samples of 13, 10, 7, and 5 patients. 81 Furthermore, 3 of the 4 randomized controlled trials did not have a follow-up period past 2 months, with only 1 study 78 reporting data up to 6 months after operation. 81 Given these limitations, there is a need for more adequately powered long-term investigations to confidently delineate an evidence-based protocol using MI training in the ACLR population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was limited evidence about strength gains among musculoskeletal disorders [ 16 ]. To date, only one study supported the positive effect of MI after anterior cruciate ligament reconstruction [ 30 ]. In our study, we found that four out of six included studies supported the positive effect of MI, which has not been confirmed previously.…”
Section: Discussionmentioning
confidence: 99%